2012
DOI: 10.1021/ol300281p
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Ligands as Promoters in PdII/0-Catalyzed C–H Olefination Reactions

Abstract: Commercially available pyridine ligands can significantly enhance the rate, yield, substrate scope, and site selectivity of arene C-H olefination (Fujiwara-Moritani) reactions. The use of a 1:1 ratio of Pd/pyridine proved critical to maximize reaction rates and yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 43 publications
4
111
0
12
Order By: Relevance
“…4449 Empirically, it is observed that heterocycles with higher expected Lewis basicities lead to lower overall product conversion in both C–H oxidation methods, which may be related to coordination-related reduction of reaction rates. Efforts are currently underway to elucidate the heterocycle–Pd(II) speciation as well as to study rates of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…4449 Empirically, it is observed that heterocycles with higher expected Lewis basicities lead to lower overall product conversion in both C–H oxidation methods, which may be related to coordination-related reduction of reaction rates. Efforts are currently underway to elucidate the heterocycle–Pd(II) speciation as well as to study rates of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[74] In ähnlicher Weise berichteten auch Sanford und Mitarbeiter kürzlich über den positiven Effekt von Pyridinliganden auf Geschwindigkeit und Selektivität oxidativer Kupplungen zwischen einfachen Arenen und Acrylaten. [75] Anhand von oXylol als Modellsubstrat wurde dabei der Einfluss der Ligandeneigenschaften auf die Regioselektivität der Reaktion gezeigt (Schema 17). Dies demonstriert einmal mehr, wie ein entsprechendes Katalysatordesign nahezu selektive C-HAktivierungen ermçglicht.…”
Section: Methodsunclassified
“…Einfluss von Pyridinliganden auf die Regioselektivität der Olefinierung von o-Xylol. [75] Schema 18. Olefinierung von Brombenzolderivaten von Glorius et al [a] Zur Vereinfachung sind die Ausbeuten der Nebenprodukte nicht angegeben.…”
Section: Carboxylierung Einfacher Areneunclassified
“…Monodentate pyridine derivatives are especially common; 2 however, catalysts containing these ligands are often susceptible to decomposition, especially at elevated temperatures. 3 Catalyst stability can be enhanced through the use of bidentate ligands, such as 2,2'-bipyridine (bpy) and 1,10-phenanthroline (phen) derivatives. These ligands have been used effectively in Pd-catalyzed aerobic oxidation reactions, although the results are typically observed in polar solvents (e.g., H 2 O, DMSO, DMF) 4 or at high temperatures (120–200 °C), 5 which are often needed to enable anionic ligand dissociation from (N~N)PdX 2 species to access open coordination at the Pd II center.…”
Section: Introductionmentioning
confidence: 99%